Assessment of tissue elasticity on different shear wave ultrasound elastography (SWE) modalities / Nur Amirah Amir - Nur Amirah, Amir (2018)
Shear wave elastography (SWE) is one of the new elastography imaging technique s which uses ultrafast ultrasound to measure and visualise tissue elasticity. This study was conducted to measure and verify the SWE measurement in a gelatine-based elasticity phantom. Five spherical inclusions of different sizes (2.9 cm and 4.5 cm) and different masses were constructed by mixing (5 to 25 g with 5 g increments) gelatine with 0.5 g of CaCO3 (as scatterer) in 150 ml of distilled water. Different amounts of gelatine represent different stiffness of lesions. 80 g of gelatine was used to construct background phantom which was mixed with 800 ml of water. The lesions were placed inside the background phantom at two different depths of different containers. The lesions’ elasticity was measured using three elastography modalities; Ultrasound Philips (iU22, Philips, USA), Ultrasound Supersonic (Aixplorer V6, Supersonic Imagine, France) and Fibroscan® (Fibroscan 502 Touch, Echosense, France). There were then compared with the gold standard measurement from a tensile testing machine Instron (Model 5969 Dual Column, Instron Co, USA). Elasticity measured using the Supersonic method showed stronger correlation than elasticity measured using Ultrasound Philips. No valid measurement was obtained from Fibroscan®, however an examination was performed on a volunteer to observe the procedure in Fibroscan and the elasticity value. The modulus of elasticity measured using Instron microtester were 1.6, 5.39, 11.84, 15.17 and 63.57 kPa respectively. The comparison between SWE ultrasound showed no significant difference (p>0.05) for 4.5 cm lesions at both 2 cm and 5 cm depth. There was a significant difference (p<0.05) of mean of elasticity between both ultrasound and Instron microtester. Results also showed that the tissue elasticity was overestimated for both ultrasound when compared with the gold standard